Assessment of Students’ Ability to Prepare Outcome-Based Education Lecture Presentation Materials - Danim, Sudarwan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to evaluate students’ ability to prepare OBE-based lecture presentation material. Carried out with a qualitative approach, the subject of this research was presentation material from the students of doctor of education study program, FKIP Universitas Bengkulu for the subject of Comparison of Education Systems Between Countries. The research results prove: (1) the learning objectives formulated by students are directly related to the material contained in the references, but the touch is still weak on the vision and mission of the study program or institution; (2) the material presented has quite strong relevance to the formulation of learning objectives; (3) there are four aspects that stand out in presentation material, namely those related to clarity, flexibility, comparison, and involvement; (4) internal and external support is still weak for the possibility of transforming learning outcomes; (5) the strategy for transforming best practices in many countries into the Indonesian situation has been touched upon quite well; and (6) the results of the assessment and feedback on the lecture material are a separate focus.